Empowerment of Integrated Family Service Posts as Herbal Corners to Increase Community Immunity - Zahroh, Chilyatiz; Nerisafitra, Paramitha; Noventi, Iis; Ainiyah, Nur (STIKes Patria Husada Blitar, 2024)
Current developments are also accompanied by an increase in the number of infectious diseases, especially tuberculosis (TB). Even though there has been a lot of research related to the treatment and management of TB, this has not been able to eliminate TB morbidity. Apart from treatment, preventing TB transmission and increasing community immunity are also determinants of TB morbidity rates. The Bangkingan Community Health Center's Traditional Medicine and Health Promotion Division, along with the Great Surabaya Cadre of Bangkingan Village, participated in community service projects in RW Hall 3, Bangkingan Village. Activities related to community service encompass mentoring, training, technology use, outreach, assessment, and program sustainability. The Bangkingan Village community has improved its knowledge, behavior, and proficiency in using herbs to boost immunity as a result of performing community service. creation of the Herbal Corner Web as a hub for herbal knowledge for preventative and promotional initiatives. Every RW has a herbal garden where one can grow therapeutic plants, and there is equipment available to make herbal remedies (powder/instant). The sustainability of the program depends on the motivation of the Great Surabaya Cadres of Bangkingan Village, so good cooperation between the Cadres is needed to continue the benefits of the program. Through the traditional medicine and health promotion division, it is necessary to provide assistance to the community regarding promotive and preventive efforts. Government support for community activities/programs in relation to improving health status needs to be increased.